2018
DOI: 10.1177/1043454218794667
|View full text |Cite
|
Sign up to set email alerts
|

The Balancing Act: Mothers’ Experiences of Providing Care to Their Children With Cancer

Abstract: The effect of pediatric cancer and its treatment are overwhelming-these effects are multifaceted and felt by the entire family unit throughout the diagnosis and treatment process. Children experience a plethora of effects as a result of the treatment process; however, it is imperative to remember that a pediatric cancer diagnosis affects parents physically, emotionally, and psychologically as well. While much of the pediatric cancer treatment occurs at the hospital or in clinics, parents are often faced with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…Sometimes they had to wait for the healthcare professionals from the hospital and felt that it would have been easier to go to the hospital instead. This is in line with the findings of Molinaro and Fletcher [ 32 ] who revealed that parents need to reprioritize their time in order to adapt to the new situation. They found it difficult to juggle the demands of life.…”
Section: Discussionsupporting
confidence: 91%
“…Sometimes they had to wait for the healthcare professionals from the hospital and felt that it would have been easier to go to the hospital instead. This is in line with the findings of Molinaro and Fletcher [ 32 ] who revealed that parents need to reprioritize their time in order to adapt to the new situation. They found it difficult to juggle the demands of life.…”
Section: Discussionsupporting
confidence: 91%
“…In the existing studies, parents of children with cancer have reported difficulties in combining work with caring for the ill child, as well as for others in the family, due to significant disruptions in the everyday life (Granek et al, 2012;Long & Marsland, 2011;Molinaro & Fletcher, 2018;Peikert et al, 2020;Wakefield et al, 2014). Parents of children with cancer have to reorganize roles and responsibilities for childcare and work, with mothers often taking primary responsibility of the ill child (Clarke et al, 2009;Long & Marsland, 2011;Molinaro & Fletcher, 2018). The most pronounced changes in role reorganization usually takes place during the initial stages of diagnosis and early treatment (Long & Marsland, 2011), although difficulties in managing the increased caregiving demands may last longterm (Peikert et al, 2020).…”
mentioning
confidence: 99%
“…Still, to gain increased understanding of the impact of childhood cancer on family life, studies that explore parents' experiences of the challenges related to work and family are needed. With this study, we wanted to capture the experiences that are more commonly shared by parents of children with cancer, without restricting the research to, for example, mothers (Molinaro & Fletcher, 2018), single parents (Granek et al, 2012) or parents of survivors (Peikert et al, 2020).…”
mentioning
confidence: 99%
“…Na Colômbia, a incidência aumentou entre 2002 e 2006, resultando em 70.877 novos casos no período (PALACIO C, et al, 2018). A Indonésia alcançou uma progressão anual de 7%, com 16.291 casos (AZIZA YDA, et al, 2019). No Brasil, de 2016 a 2017, foi estimado em 12.600 novos casos nessa faixa etária (ABDOLJABBARI M, et al, 2018;MEDEIROS EGMS, et al, 2019).…”
Section: Submetido Em: 7/2020 | Aceito Em: 8/2020 | Publicado Em: 3/2unclassified